(3bhJ GdbdhHs - (3CHh WGdH Gdecj , eMeO Hf Ydj Hf YWjI GdMGQKj, CHh WGdH Gdecj,J (B386 (3g` s ((3eMeO Hf GdMSf Hf efUhQ s)
(3ChdgG (B:s
(3jHJOF HTQM ebGe GdJhcd hhUa GdeJhcdjf s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B27s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B177 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1361s
Keywords: (3GdJUha hGdBOGH GdTQYjIs